League of Women Voters (U.S.) records - League of Women Voters (U.S.); National American Woman Suffrage Association. League of Women Voters; National League of Women Voters (U.S.)
Correspondence, memoranda, minutes, proceedings, speeches, reports, project studies, subject files, biographical material, financial records, newspapers clippings, printed matter, and other records concerning the league's activities at the national, state, and local levels. Documents the organization's lobbying efforts, national conventions and council meetings, and projects of the League of Women Voters Education Fund. Topics include child labor and welfare, citizen participation in the inner cities, civil rights, civil service, consumer issues, education, election law, environment, ERAmerica and the Equal Rights Amendment, federal-state relations, health, housing, immigration, international relations and trade, labor, military spending, national security, patriotism, needs and rights of the poor, race relations, the suffrage movement, United Nations, voter education, water quality and related land use, welfare, and women's legal status and rights.
Microfilm edition produced by University Publications of America, Inc., available for selections from records at the League's national headquarters, Washington, D.C., and the Library of Congress Manuscript Division
Microfilm of originals in: League of Women Voters (U.S.) national headquarters and the Library of Congress Manuscript Division (Washington, D.C.).
League of Women Voters (U.S.) national headquarters and Library of Congress Manuscript Division
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
National American Woman Suffrage Association formed in February 1919; in 1920 the association's section, League of Women Voters, became an independent organization under the name National League of Women Voters (later the League of Women Voters of the United States).
Keywords: United States; ERAmerica (Organization); League of Women Voters (U.S.). -- Education Fund; United Nations; Child welfare; Child labor; Citizen participation; Civil rights; Civil service; Constitutional amendments -- United States; Consumer protection; Education; Election law; Emigration and immigration; Environmental protection; Equal rights amendments; Federal government; Health; Housing; Inner cities; International relations; International trade; Labor; Land use; National security; Patriotism; Poor; Public welfare; Race relations; State governments; Suffrage; Voting; Water quality; Women -- Legal status, laws, etc; Women's rights